Cancer of the corpus of the uterus – diagnostic markers and monitoring of the desease - Wojcierowski, Jacek; Futyma, Konrad; Tomasz Putowski, Lechosław; Kubiatowski, Tomasz (Menopause Review/Przegląd Menopauzalny, 2005)
Endometrial cancer is one of the most common gynecological malignancy in Poland. According to National Cancer Registry data, more than 10000 women had gynecological cancer and more than 3000 had uterine corpus cancer in 1998. Main cause of cancer development is age and hormonal condition. Diabetes, hypertension, obesity, sterility, low birth number, late manopause and genetic factors increase risk of cancer developement. Radical surgery is main therapy and had to be complemented by combination of radiotherapy, hormotherapy or chemiotherapy depending on histological type and clinical stage of the desease. Aim of this paper is to present molecular biology methods of diagnosis and monitoring of the desease. Pre and post operative levels of tumor-associated antigens like CA 125, CA 19.9, CA 15.3, CA 72.4 correlate with stage, histologic grade, lymph node status and clinical outcome, and can be very useful for post treatment surveillance. On the other hand CA 125, CD 10, HER-2/neu, FAS are known as immunohistochemical markers, and could be helpful in differential diagnosis of undifferentiated uterine sarcomas. To improve diagnostic and therapeutic process this biochemical tools and methods should be used more widely. Ideal maker for uterine corpus carcinoma has not been found, but hopefully the substance fulfiling those criteria is going to be discovered in close future.